Controlled ocular drug delivery with nanomicelles. (2nd June 2014) - Vaishya, Ravi D.; Khurana, Varun; Patel, Sulabh; Mitra, Ashim K.
<x xml:space="preserve">Abstract</x> Many vision threatening ocular diseases such as age‐related macular degeneration (AMD), diabetic retinopathy, glaucoma, and proliferative vitreoretinopathy may result in blindness. Ocular drug delivery specifically to the intraocular tissues remains a challenging task due to the presence of various physiological barriers. Nonetheless, recent advancements in the field of nanomicelle‐based novel drug delivery system could fulfil these unmet needs. Nanomicelles consists of amphiphilic molecules that self‐assemble in aqueous media to form organized supramolecular structures. Micelles can be prepared in various sizes (10–1000 nm) and shapes depending on the molecular weights of the core and corona forming blocks. Nanomicelles have been an attractive carrier for their potential to solubilize hydrophobic molecules in aqueous solution. In addition, small size in nanometer range and highly modifiable surface properties have been reported to be advantageous in ocular drug delivery. In this review, various factors influencing rationale design of nanomicelles formulation and disposition are discussed along with case studies. Despite the progress in the field, influence of various properties of nanomicelles such as size, shape, surface charge, rigidity of structure on ocular disposition need to be studied in further details to develop an efficient nanocarrier system. For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.